DEVELOPMENT OF NGAWUWUH TRADITION TO INCREASE EMPATHY IN IBNU KATSIR 2 - Yanti, Yanti; Rahmawati, Weni Kurnia; Nafisah, Hilya (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
This study aims to examine and develop the tradition of Ngawuwuh as an effective method for enhancing empathy among the students (mahasantri) at Pondok Pesantren Ibnu Katsir. Ngawuwuh, which is a tradition of sharing and giving without expecting anything in return, holds noble values that are relevant to character building and empathy. However, this tradition has started to erode due to the influence of modern lifestyles, which tend to be individualistic, as well as the lack of meaningful social interactions among the younger generation, including the mahasantri. The decline in empathy among mahasantri is the main issue addressed in this research. In the pesantren environment, which should ideally be one that educates and fosters good character, challenges have emerged in maintaining and developing empathy amidst external influences such as technology and individualism. This highlights the need for a more focused character education method, such as through the development of the Ngawuwuh tradition. The general aim of this research is to develop the Ngawuwuh tradition as an educational strategy to enhance empathy among the mahasantri at Pondok Pesantren Ibnu Katsir. This study is expected to produce innovative and relevant character education methods, as well as restore the role of local traditions as an important tool in shaping personality and positive social values among the younger generation. Keywords: empathy, ngawuwuh, module.